Mathematical modelling of the thermal and hydraulic behaviour of plate heat exchanger in the fouling conditions - Kapustenko, Petro Oleksiyovych; Demirskiy, O. V.; Tovazhnyanskyy, Leonid Leonidovich; Klemeš, Jiří Jaromír; Matsegora, O. I.; Arsenyev, Pavlo Yurievich; Arsenyeva, Olga Petrovna (The Italian Association of Chemical Engineering, 2018)
The mathematical model of Plate Heat Exchanger (PHE) subjected to fouling is proposed. It is represented by the system of ordinary differential equations. The model is accounting for the distribution of process parameters along the PHE channel that allows predicting fouling development in time at different locations along the channel length. The development of the fouling deposit is accounted with the fouling model presented by the equation in dimensionless form. The relative influence of different terms is characterized by empirical coefficients which can be identified with the data of monitoring the PHE thermal and hydraulic performance. The model allows also the prediction of pressure drop variation in PHE with the development of fouling deposition layer and respective reduction in channels cross-section area. The application of the model and its accuracy is demonstrated with two case studies considering the monitoring of PHEs thermal and hydraulic performance in the industry at sugar factory and in District Heating system.